THE ROLE OF THE BEKASI CITY MANPOWER OFFICE IN DETERMINING THE CITY MINIMUM WAGE (UMK) - Herlyansyah, Bayu; Priyadi, Budi Puspo; Djumiarti, : Titik; Rostyaningsih, . Dew (Journal of Public Policy and Management Review, 2021)
Manpower is everything that is related to labor before, during, and after the working period. In Indonesia, one form of the government's role in the manpower sector is under the auspices of the Ministry of Manpower. As a state apparatus in charge of serving citizens, the Ministry of Manpower is assisted in carrying out its duties by the local government, especially the Manpower Office. The manpower office is a government institution that has functions in fostering, controlling rights & obligations as well as supervision in the manpower sector. Wages are a right that must be fulfilled by job providers to workers after carrying out their obligations as workers. The results of the discussion of the role of the Bekasi City Manpower Office in determining the city minimum wage (UMK) for the city of Bekasi can be categorized as good due to the role given by the Bekasi City Manpower Office. The role played by the Bekasi City Manpower Office is as a facilitator, regulator and catalyst. In addition, the Bekasi City Manpower Office also plays a role in creating a harmonious relationship between workers and employers. Conclusion The Bekasi City Manpower Office has carried out its role well in the process of determining the city minimum wage (UMK) for the city of Bekasi, but it is hoped that the Bekasi City Manpower Office can increase its role again by conducting an evaluation, this is done so that in the future every year it can minimize mistakes that had happened in the previous year.